WADI: A Livelihood Programme for tribal development - Sohani, Girish G (Indian Farming, 2015)
A comprehensive tribal development programme has been taken up by BAIF in southern Gujarat, western Maharashtra, southern Rajasthan and southern Karnataka. This programme called Wadi consists of an activity of rasing a horti-forestry orchard by the tribal families on sloping uplands. The land is shaped and brought under intercrops in the monsoon and if possible in winters and summers with small-scale irrigation. With other linkage activities the programme has helped the tribals by providing stable markets, add value to the tribal produce and generated livelihood and income.